Analysis of microarray-identified genes and MicroRNAs associated with Trifluridine resistance in colorectal cancer. Issue 1 (31st December 2022) - Zhang, Qiqi; Wang, Zhan; Zhang, Zhenghua; Zhu, Lifei; Yang, Xijing
Abstract : Trifluridine (FTD) is an effective drug for advanced colorectal cancer (CRC); however, the molecular mechanisms underlying FTD resistance has not been elucidated. This study aimed to explore mRNAs and microRNAs (miRNAs) associated with FTD resistance in CRC. The analyzed data were downloaded from the Gene Expression Omnibus (GEO) database. The differentially expressed- mRNAs (DEGs) and miRNAs (DEMs) between FTD-resistant and parental cell lines were screened. Next, the DEGs-related miRNAs were predicted and then DEGs-DEMs network was constructed, followed by functional enrichment analysis and protein–protein interaction (PPI) analysis. Meanwhile, the gene–drug interactions were identified. Finally, the prognostic significance of key genes was evaluated using survival analysis. A total of 23 DEMs and 928 DEGs were screened between FTD-resistant and CRC parental cells. The DEMs-DEGs network revealed that miRNAs such as hsa-miR-3714 and hsa-miR-3678-3p with higher degrees, and PPI network indicated that genes like HDAC5, ETV6, CCNF, SREBF1, and LDLR might be recognized as hub genes. Moreover, we observed that CCNF, HDAC5, ETV6, and SREBF1 were associated with the overall survival or disease-free survival of patients with CRC. These findings might provide an insight into potential therapeutic targets and druggable genes for FTD-resistant in patients with CRC.